Alleviating Poverty through Islamic Microfinance: Outreach and Efficiency (Study on BMT and Islamic Cooperatives in Indonesia) - Purwanto; Ina Primiana; Dian Masyita; Erie Febrian (Экономика региона, 2020)
The involvement of Islamic Microfinance Institutions (IMFI) in building the national economy is paramount to help the poor. However, provision of access and services to lower-level households can potentially conflict with the sustainability of the institutions. This study analyses the social outreach factors that determine financial and social efficiencies. To reach the set goal and solve this issue, we used mixed methodology combining quantitative (statistical instruments, such as Data Envelopment Analysis (DEA) and multivariate analysis) and qualitative approaches (interviews to clarify or deepen the existing information). The assessment of the dependent variables is influenced by proxies of depth, breadth, length, scope, and cost. The results showed that the average loan instalments and the number of offices and branches significantly influence financial and social efficiency. The age of the institution only has an effect on financial efficiency. Simultaneously, profit orientation, the amount and type of financing and the amount and type of savings only have a high impact on social efficiency, whereas the impact of fund collection and cost per borrower is insignificant. There is a strong positive correlation between the two dependent variables. The influence of independent variables on financial and social efficiency is significant with the coefficient of determination 23.1274 % and 53.2941 %, respectively.